FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA DEFISIENSI ZAT BESI PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS OEPOI KOTA KUPANG TAHUN 2012 - Nawa, Lusianus; Picauly, Intje; Nur, Marselinus Laga (Jurnal Pangan Gizi dan Kesehatan, 2013)
Pregnant women is one the groups vulnerable to malnutrition because of the intake of food containing low iron in pregnant women. This is caused by ignorance about the importance of consuming food containing iron and iron tablets for the sake of pregnancy. Apart from this, family income and frequency of antenatal care (ANC) may have indirectly caused the incidence of iron-nutrition anemia on pregnant women. This research is aimed at finding out factors related to incidence of anemia deficiency of iron in pregnant women in the work areas of Puskesmas Oepoi. The research is of an analytic-survey one with a design of cross-sectional study. All pregnant women in the work areas of Puskesmas Oepoi have been used of which 91 of the population have been sampled by cluster sampling technique. Statistic analysis uses Chi Square test. Statistic test shows the following result: there is a relation between the knowledge of nutrition and the pregnant women (p=0,008, p<0,05), family income (p=0,000, p<0,05), food consumption pattern or diet in this respect (p=0,000, p<0,05), and frequency and quality of ANC (p=0,000, p<0,05) on anemia deficiency of iron in pregnant women.